Chiral ionic liquid assisted synthesis of some metal oxides. Issue 2 (5th January 2017) - Husanu, Elena; Cappello, Valentina; Pomelli, Christian Silvio; David, Jeremy; Gemmi, Mauro; Chiappe, Cinzia
Abstract : A chiral ionic liquid with a natural alcohol based chain was used as a tailoring agent for the synthesis of simple and cost effective materials such as ZnO, CuO, CuO–ZnO with peculiar morphology. Abstract : A chiral ionic liquid with a natural alcohol based chain was used as a tailoring agent for the synthesis of simple and cost effective materials such as ZnO, CuO, CuO–ZnO with peculiar morphology. The morphology and chemical composition of the microstructures were investigated by bright-field and scanning transmission microscopy (BF-TEM and STEM), energy dispersive X-ray spectroscopy (EDX), Fourier transform infrared spectroscopy (FTIR), and UV-VIS spectroscopy. Furthermore, the photocatalytic activity of ZnO, CuO and ZnO–CuO nanostructures was quantified for methylene blue (MB) dye. CuO needles had the lowest photocatalytic activity (23.8% in 40 min). Due to their peculiar forms, ZnO (flower like shape) and ZnO/CuO (leaf like shape where ZnO nanoparticles were deposited) had the highest photocatalytic activity in 40 min (93.6% for ZnO nanoparticles and 95% for ZnO–CuO nanostructures).